CLIC1 null mice demonstrate a role for CLIC1 in macrophage superoxide production and tissue injury - Ulmasov, Barbara (Physiol Rep, 2017)
We generated and studied CLIC1 null (C1KO) mice to investigate the physiological role of this protein. C1KO and matched wild‐type (WT) mice were studied in two models of acute toxic tissue injury. CLIC1 expression is upregulated following acute injury of WT kidney and pancreas and is absent in C1KOs. Acute tissue injury is attenuated in the C1KOs and this correlates with an absence of the rise in tissue reactive oxygen species (ROS) that is seen in WT mice. Infiltration of injured tissue by inflammatory cells was comparable between WT and C1KOs. Absence of CLIC1 increased PMA‐induced superoxide production by isolated peritoneal neutrophils but dramatically decreased PMA‐induced superoxide production by peritoneal macrophages. CLIC1 is expressed in both neutrophils and macrophages in a peripheral pattern consistent with either plasma membrane or the cortical cytoskeleton in resting cells and redistributes away from the periphery following PMA stimulation in both cell types. Absence of CLIC1 had no effect on redistribution or dephosphorylation of Ezrin/ERM cytoskeleton in macrophages. Plasma membrane chloride conductance is altered in the absence of CLIC1, but not in a way that would be expected to block superoxide production. NADPH oxidase redistributes from an intracellular compartment to the plasma membrane when WT macrophages are stimulated to produce superoxide and this redistribution fails to occur in C1KO macrophages. We conclude that the role of CLIC1 in macrophage superoxide production is to support redistribution of NADPH oxidase to the plasma membrane, and not through major effects on ERM cytoskeleton or by acting as a plasma membrane chloride channel.